MR Imaging Characteristics and Neuropathology of the Spinal Cord in Adult-Onset Autosomal Dominant Leukodystrophy with Autonomic Symptoms - Sundblom, J. (AJNR Am J Neuroradiol, 2009)
BACKGROUND AND PURPOSE: MR imaging findings in adult-onset autosomal dominant leukodystrophy (ADLD) with autonomic symptoms have been described in the brain, but no descriptions of MR imaging findings in the spinal cord have been published. Here, we describe MR imaging findings in the spinal cord in adult-onset ADLD with autonomic symptoms and histopathologic investigations of the spinal cord. MATERIALS AND METHODS: Twelve subjects from 2 families with adult-onset ADLD with autonomic symptoms identified by clinical investigation underwent MR imaging examination of the spinal cord. Sagittal and transverse sections were obtained. MR imaging examination of the brain was performed in 11 patients. One of the patients underwent postmortem examination, and the spinal cord was subjected to histopathologic analysis. RESULTS: In all family members with adult-onset ADLD with autonomic symptoms, even in the asymptomatic person, the spinal cord was thin. All examined family members also had a slight general white matter signal intensity (SI) increase in the whole spinal cord, mainly visible in T2-weighted transverse images. The pathologic examination revealed a discrete demyelination in the spinal cord. Brain MR imaging also showed increased T2 SI in the white matter. CONCLUSIONS: The spinal cord is affected in adult-onset ADLD with autonomic symptoms. Findings consist of atrophy and a diffuse T2 SI increase in the white matter. Transverse images are needed to assess these findings. The typical SI changes of the spinal cord are also present in subjects without clinical symptoms of the disease and with very limited changes in the brain.